(untitled) (Research, Society and Development, 2021)
Objective: To know the predisposition for Burnout Syndrome in the nursing team in critical sectors in a hospital of medium philanthropic complexity in eastern São Paulo and to correlate this predisposition with their sociodemographic profile. Method: Field study, exploratory, quantitative, of intentional probabilistic sampling, whose data were collected via the Maslach Burnout Inventory (MBI) instrument, in nursing professionals allocated in the Neonatal and Adult ICU services, Intermediate Care Unit - Adult and Neonatal ( UCI and UNCI), Emergency Room and Surgical Center, as these sectors provide the most complex assistance in the hospital in question. Results: 83 nursing professionals participated in this study. Sociodemographic profile showed prevalence of females, age group between 26 to 40 years, position of nursing technician and time of training and function above 05 years. The presence of BS in the study sample showed a low level for the dimensions emotional exhaustion and depersonalization and a moderate level for professional achievement. Conclusion: The relationship between predispositions to Burnout Syndrome in the nursing team in critical sectors where the study was conducted was present.